Effect of Pleurotomy During Internal Mammary Artery Harvest on Pulmonary Function - Rahim, AMA; Kibria, G; Ahmed, NU (Cardiovascular Journal, 2011)
Background: Pulmonary function after coronary artery bypass graft surgery using harvested Internal mammary artery(IMA) were assessed in this prospective case control Clinical study comparing two groups of Patients with or without pleurotomy. Method: we conducted this Study at National Institute of Cardiovascular Diseases (NICVD), Dhaka, in the Department of Cardiovascular Surgery.A total of 60 consecutive patients undergoing CABG with use of IMA between july 2005 to June 2007 were reviewed. Study population were divided into Group A (n=30,undergone CABG with pleurotomy during IMA harvestion).Group B (n=30,undergone CABG with intactpleura during IMA harvestion). Results: in lung function spirometry revealed FEV1 significantly decreased in group A than B (56.81±17.76% Vs 79.85±7.7%; p=0.035)and when FEV1correalated with inspiratory vital capacity the advantage of intact pleura were confirmed at 6th postoperative day (78.02 ±12.17; B, 82.08 ±11.72 p=0.045). Vital capacity was significantly decreased in-group A than B at 3 months postoperatively (A 88.79 ± 14.38%;B 98.11±30.25%; p=0.009), but not on 6th Postoperative day. Pleuropulmonary complication like atelectasis, pleural effusion insignificantly higher in groupA than B(16.7 %VS6.7%) and (10% vs. 6.7%)at 6th postoperative day but not at 3months postoperatively. Conclusions: These results demonstrate that pleurotomy during Internal mammary artery harvesting significantly deteriorated pulmonary function variably than intact pleura group of patients Keywords: Pleurotomy; Internal mammary artery(IMA); Pulmonary function; CABG DOI: http://dx.doi.org/10.3329/cardio.v3i2.9186 Cardiovasc. J. 2011; 3(2): 163-168